Resistência de genótipos de soja a Dichelops melacanthus (Dallas)(HEMIPTERA: PENTATOMIDAE) - Canassa, Vinícius Fernandes [UNESP] (2015)
Soybean [Glycine max (L.) Merrill] is subject to attack by insect pests from germination to harvest. In the growth vegetative phase, the crop is target of several defoliating caterpillars. Moreover, in the reproductive phase, it suffers from stink bugs complex attack (Pentatomidae family). These insects feed directly from the pods and seeds, causing damage from the early development of these bodies to maturity. The species Dichelops melacanthus (Dallas, 1851) is an important pest for several crops in southern Brazil, especially north of Paraná State. This insect is still considered a secondary pest of soybean, but increasing infestations have been observed. In addition, it is highlighted as key-pest of maize [Zea mays (L.)], wheat [Triticum aestivum (L.)] and other grasses such as oat [Avena strigosa (Schreb.)] and triticale [(Triticum secale (Wittmack)]. Considering the lack of efficient control methods, in special those less harmful to the environment, this study evaluated 17 soybean genotypes from three maturity groups (early, semi-early and late), to characterize resistance mechanisms to the green-belly stink bug. Therefore, attractiveness tests were carried out, as well as food preference and biological performance under laboratory conditions (T= 26  2ºC, R.H. = 65  10% and photoperiod=14h). Pods of genotypes PI 171451 and D 75-10169 (early); PI 227687, 'IAC 100', IAC 78-2318 and IAC 74-2832 (semiearly) were unattractive and consumed by adult of D. melacanthus, indicating the occurrence of antixenosis. In adittion, pods of PI 274453, PI 274454 and L 1-1-01 (late) showed lesser number of bites, indicating expression of the same mechanism. All materials affected the biological performance of the green-belly stink bug, characterizing the occurrence of antibiosis. However, PI 227687, 'IAC 100', PI 171451, IAC 78-2318, D 75-...